2016
DOI: 10.1002/mnfr.201501025
|View full text |Cite
|
Sign up to set email alerts
|

Obese ZDF rats fermented resistant starch with effects on gut microbiota but no reduction in abdominal fat

Abstract: Scope To determine if whole-grain (WG) flour with resistant starch (RS) will produce greater fermentation than isolated RS in obese Zucker Diabetic Fatty (ZDF) rats, and whether greater fermentation results in different microbiota, reduced abdominal fat, and increased insulin sensitivity. Methods and results This study utilized four groups fed diets made with either isolated digestible control starch, WG control flour (6.9% RS), isolated RS-rich corn starch (25% RS), or WG corn flour (25% RS). ZDF rats ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
3
26
0
2
Order By: Relevance
“…We conclude that increases in M. smithii and S24‐7 are markers of bacterial fermentation of RS because both rat phenotypes had similar amounts of these potential markers in phase 1 when no RS was fed. We previously observed increased S24‐7 in Zucker diabetic fatty (ZDF) rats with obesity that robustly fermented RS , and we hypothesize that we would have observed an increase in M. smithii if these were measured in other studies. Increases in S24‐ 7 and M. smithii may be under a homeostatic mechanism of host dynamics that regulates the gut community responses to promote host fermentation.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We conclude that increases in M. smithii and S24‐7 are markers of bacterial fermentation of RS because both rat phenotypes had similar amounts of these potential markers in phase 1 when no RS was fed. We previously observed increased S24‐7 in Zucker diabetic fatty (ZDF) rats with obesity that robustly fermented RS , and we hypothesize that we would have observed an increase in M. smithii if these were measured in other studies. Increases in S24‐ 7 and M. smithii may be under a homeostatic mechanism of host dynamics that regulates the gut community responses to promote host fermentation.…”
Section: Discussionmentioning
confidence: 70%
“…Cecal contents were frozen in liquid nitrogen and stored at −80°C. Fermentation (cecum weights, cecal content pH and short‐chain fatty acids [SCFAs], and serum glucagon‐like peptide 1 [GLP‐1] active) was measured as described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were humanely euthanized by isoflurane induction and cardiac exsanguination after 3 weeks on the diets. Blood was collected in tubes containing DPP‐4 inhibitor for measurement of active GLP‐1 using ALPCO ELISA kit (Salem, NH) as was previously reported . The stomach, small intestine, cecum, and large intestine were separated and weighed individually full and empty.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has found that RS2, a high‐amylose maize starch, is robustly fermented by several different rodent models, including young, male Sprague‐Dawley rats when fed a moderate‐ or low‐fat diet . Although there has been phenotypic variation in body weight changes and fat accretion, male Sprague‐Dawley, obese Zucker Diabetic Fatty (ZDF), and CD obese‐prone rat models have distinctly demonstrated robust fermentation of Hi‐Maize 260 high amylose starch as indicated by enlarged ceca, decreased cecal pH, and increased production of SCFAs . Martinez et al.…”
Section: Introductionmentioning
confidence: 99%